Axial resistance of open-ended pipe pile driven in gravelly sand. Issue 2 (1st March 2019) - Han, Fei; Ganju, Eshan; Prezzi, Monica; Salgado, Rodrigo; Zaheer, Mir
Abstract : A full-scale, double-wall, open-ended pipe pile with a diameter, B  = 660 mm was densely instrumented with a combination of electrical-resistance and vibrating-wire strain gauges. The test pile was driven into a gravelly sand soil profile to a depth of 30·48 m and then statically and dynamically load tested. The double-wall instrumentation allows independent measurements of the outer shaft, inner shaft (plug) and annulus resistances during a static load test. The residual loads locked in the pile after driving were measured and considered in the correction of the resistance components. The load–settlement curve, load transfer curves and the profile of the unit limit shaft resistance were obtained from the static load test measurements. Two cone penetration test-based methods were used to estimate the resistance of the test pile, which was compared with that obtained from the static load test. Both methods provide good estimates for the unit shaft resistance in sandy layers with low gravel content (<20%), but significantly overestimate the unit shaft resistance mobilised in soil with high gravel content (>30%). The estimated base resistances by both methods match well that measured in the static load test.